OPTIMIZATION CALCULATION OF ELECTRICAL SUBMERSIBLE PUMP IN MAA-72 WELL IN X FIELD PT Y - Desi Kusrini; Arief Rahman; Adrian Indarti; Muhammad Aqil Al Munawar (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
MAA-72 well experienced a decrease in production rate, Pump IND1300 42 hz / pump ROR of 960- 1640 bfpd. Well production is Qgross 599.97 bfpd. The required data obtained are general report electrical submersible pump, reservoir data, fluid properties data, production data and wellprofile data, data obtained directly from the computer in the field. In data processing, the method is to determine the potential analysis of the well, evaluate the installed pump, and optimize the well with a new pump. Optimum results of 1498.55 bfpd, Gf 0.435 Psi/ft, IND1300 pump evaluation, namely PIP 170.37 Psi, TDH 1782.27 ft, PSD 1969.42 ft, number of stages 200 stages, EP 49% and Hp 33.5. Optimization was carried out by replacing the pump. New pump selection DN1800/60 Hz / ROR 1200-2400 bfpd, head/stage 22 ft, Hp 0.34 EP 70%. Determination of new pump PSD 2022.94 ft, PIP 43.5 Psi, TDH 2212.32 ft, number of stages 22 stages. Increase in Qact production rate (599.97 bfpd) to (1498.55 bfpd) with a rate increase of 898.58 bfpd.